2021
DOI: 10.5271/sjweh.4001
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional and national burden of disease attributable to 19 selected occupational risk factors for 183 countries, 2000–2016: A systematic analysis from the WHO/ILO Joint Estimates of the Work-related Burden of Disease and Injury

Abstract: Objectives We provide a brief introduction to the objectives, data, methods and results of the World Health Organization (WHO)/International Labor Organization (ILO) Joint Estimates of the Work-related Burden of Disease and Injury (WHO/ILO Joint Estimates), which estimated the burden attributable to 19 selected occupational risk factors. Methods The WHO/ILO Joint Estimates were produced within the global Comparative Risk Assessment framework, which attributes the burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Long working hours have a harmful effect on the health of workers and also lead to economic inefficiency. The World Health Organization (WHO) and the International Labour Organization (ILO) reported that 488 million people were exposed to long working hours in 2016, which was the occupational risk factor that caused the highest number of deaths (745,194 attributable deaths in 2016) [ 2 , 3 ]. According to the Organization for Economic Cooperation and Development (OECD) data, the average annual working hours in South Korea were 1915 h in 2021, meaning that it is one of the countries with the longest working hours among the OECD countries (the average in all OECD countries, 1716 h; the lowest in Germany, 1349 h) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long working hours have a harmful effect on the health of workers and also lead to economic inefficiency. The World Health Organization (WHO) and the International Labour Organization (ILO) reported that 488 million people were exposed to long working hours in 2016, which was the occupational risk factor that caused the highest number of deaths (745,194 attributable deaths in 2016) [ 2 , 3 ]. According to the Organization for Economic Cooperation and Development (OECD) data, the average annual working hours in South Korea were 1915 h in 2021, meaning that it is one of the countries with the longest working hours among the OECD countries (the average in all OECD countries, 1716 h; the lowest in Germany, 1349 h) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a Dutch study, 21.5% of the SA in the working population can be considered possibly avoidable, though only 13.6% of SA are attributable to work-related factors [ 15 ]. Globally, about 90 million disability-adjusted life years were attributable to occupational exposures in 2016 [ 16 ], justifying the need for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…This is the approach underpinning the WHO/ILO analysis that is reported in Pega et al’s paper ( 2 ). Estimates of relative risk for paired combinations of occupational risk factor and disease were collated with data on the population prevalence of exposure to calculate population attributable fractions (PAF) ( 3 ), which then were multiplied by estimates of the total population impact of the disease (in terms of deaths and disability-adjusted life-years) to derive burdens attributable to occupation ( 2 ).…”
mentioning
confidence: 99%
“…A second problem lies in the ambiguous specification of some risk factors. The analysis attributes large numbers of deaths from COPD to occupational exposure to “particulate matter, gases and fumes” ( 2 ). It is unclear, however, what exactly is implied by that term.…”
mentioning
confidence: 99%
See 1 more Smart Citation